2017
DOI: 10.1097/gme.0000000000000916
|View full text |Cite
|
Sign up to set email alerts
|

Long-term sertraline treatment and depression effects on carotid artery atherosclerosis in premenopausal female primates

Abstract: Objective Atherosclerosis developed during premenopausal years predicts postmenopausal atherosclerosis burden. Selective serotonin reuptake inhibitor (SSRI) antidepressants, recently approved for hot flushes, have been associated with increased ischemic stroke risk in several observational studies; however effects on carotid artery atherosclerosis, a strong predictor of future vascular events, are unknown. Methods The effects of chronic administration of a commonly prescribed SSRI, sertraline HCl, on atheros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…Importantly, epidemiological studies analyzing participants from the ARIC (Atherosclerosis Risk in Communities) study treated with SSRI antidepressants (mean age, 63 ± 10 years, followed for a median of 13.5 years) report a trend for increased risk of cardiovascular disease and stroke (hazard ratios, 1.10 and 1.07, respectively) as compared to patients treated with non-SSRI antidepressants (Almuwaqqat et al, 2019). Consistent with the aforementioned findings, previous studies demonstrate that in depressed monkeys treatment with SSRIs, such as sertraline, also significantly increases atherosclerosis in the carotids and the coronary circulation (Shively et al, 2015; Shively et al, 2017; Silverstein-Metzler et al, 2017). Importantly, recent studies demonstrate that in mouse models of atherosclerosis chronic treatment with fluoxetine also promotes atherogenesis by up-regulating vascular inflammation (Rami et al, 2018) ( Figure 1 ).…”
Section: Vascular Side Effects Of Fluoxetine and Other Ssris: Potentisupporting
confidence: 84%
“…Importantly, epidemiological studies analyzing participants from the ARIC (Atherosclerosis Risk in Communities) study treated with SSRI antidepressants (mean age, 63 ± 10 years, followed for a median of 13.5 years) report a trend for increased risk of cardiovascular disease and stroke (hazard ratios, 1.10 and 1.07, respectively) as compared to patients treated with non-SSRI antidepressants (Almuwaqqat et al, 2019). Consistent with the aforementioned findings, previous studies demonstrate that in depressed monkeys treatment with SSRIs, such as sertraline, also significantly increases atherosclerosis in the carotids and the coronary circulation (Shively et al, 2015; Shively et al, 2017; Silverstein-Metzler et al, 2017). Importantly, recent studies demonstrate that in mouse models of atherosclerosis chronic treatment with fluoxetine also promotes atherogenesis by up-regulating vascular inflammation (Rami et al, 2018) ( Figure 1 ).…”
Section: Vascular Side Effects Of Fluoxetine and Other Ssris: Potentisupporting
confidence: 84%
“…Although quetiapine and norquetiapine do not affect depression symptoms, it was demonstrated that they increased anti-inflammatory cytokine IL-10 levels and decreased pro-inflammatory cytokine IFN-y levels. 46 Although it was reported that antidepressant treatment facilitated the development of atherosclerotic plaques in the carotid, 47 other studies argued the opposite. 48 To clarify the effect of drugs on arterial stiffness, further studies are needed that would compare the use of isolated antidepressants and isolated antipsychotics and no drug use in depression patients.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed a progressive increase in atherosclerotic lesion formation by the enhancement of leukocyte adhesion to arterial walls [ 137 ]. Studies conducted in non-human primates with the treatment of depression with the SSRI, setraline, found that treatment of depression with SSRIs resulted in an almost 5-fold increase in coronary artery atherosclerosis when compared to untreated depressed monkeys, and a 6-fold increase in SSRI-treated depressed monkeys when compared to untreated wild type controls [ 138 , 139 ]. These results would indicate that (1) depression promoted the development of atherosclerotic plaque formation, (2) treatment with the SSRI agent further amplified this in depressed animals, and (3) this effect appeared to be independent of other traditional cardiovascular risk factors [ 138 ].…”
Section: Current Knowledge About the Impact Of Serotonin Modifying Dr...mentioning
confidence: 99%